223k views
4 votes
Prove that the triangle EDF is isosceles. Give reasons for your answer.

Prove that the triangle EDF is isosceles. Give reasons for your answer.-example-1

1 Answer

6 votes

Answer:

Proved

Explanation:

Required;

Prove that the above triangle is a triangle

An isosceles triangle has 2 equal sides and 2 equal angles;

But in this case, we're dealing with only angles.

Once, we can prove that triangle EDF has 2 angles, then it has been proven that it is an isosceles triangle.

The first step is to calculate
<DFE

First, it should be noted that angle on a straight line equals 180;

This implies that


<DFE + 90 + (y)/(2) = 180

Subtract
90 +(y)/(2) from both sides


<DFE + 90 + (y)/(2) - ( 90 + (y)/(2))= 180 - ( 90 + (y)/(2))


<DFE + 90 + (y)/(2) - 90 - (y)/(2)= 180 - 90 - (y)/(2)


<DFE = 90 - (y)/(2)

The next step is to calculate the measure of
<DE F

It should be noted that angles in a triangle add up to 180;

This implies that


<DE F + <DFE + <EDF = 180

Where


<EDF = y --- (Given)\\<DFE = 90 - (y)/(2) --- (Calculated)


<DE F + <DFE + <EDF = 180 becomes


<DE F + 90 - (y)/(2) + y = 180

Subtract 90 from both sides


<DE F + 90 - (y)/(2) + y - 90 = 180 - 90


<DE F - (y)/(2) + y = 90

Perform arithmetic operation on y and -y/2


<DE F + (-y +2y)/(2) = 90


<DE F + (y)/(2) = 90

Subtract y/2 from both sides


<DE F + (y)/(2) - (y)/(2) = 90 - (y)/(2)


<DE F = 90 - (y)/(2)

At this point, it has been proven that triangle EDF is isosceles because
<DE F = <DFE = 90 - (y)/(2)

User GoldRoger
by
5.8k points